Boston Studies in the Philosophy of Science
496 p.
Keywords: In this fifth volume of Boston Studies in the Philosophy of Science, we have gathered papers about the logic and methods of the natural sciences. Along with the individual pieces, there are several which have originated as commentaries but are now supplementary contributions: those by Stachel and Putnam. Grlinbaum's long essay developed from a paper first suggested for our Colloquium some years ago, and we are glad of the occasion to publish it here. Several of the papers were not first presented to our Colloquium but they are the work of friends and scholars who have contributed to our discussions along similar lines. We are grateful to them for allowing us to publish their papers: L Bernard Cohen, Hilary Putnam, Mihailo Markovic. And we are also grateful to C. F. von Weizsacker for his paper, recently presented to the Boston philosophical and scientific community as a lecture at M. LT. With these few exceptions, the fifth volume presents work which was partially supported by a grant from the U. S. National Science Foundation to Boston University. Such support will conclude with the fourth volume of philosophical studies of psychology, the social sciences, history, and the inter-relationships of the sciences with ethics and metaphysics. Unimportant circumstances made it necessary to publish that fourth volume after this fifth volume, and perhaps this will mildly suggest that neither science nor the philosophy of science needs to be constrained by orthodoxy of procedure.